The Anopheles gambiae cE5, a tight- and fast-binding thrombin inhibitor with post-transcriptionally regulated salivary-restricted expression - Ronca, Raffaele (2012)
Mosquito saliva carries a large number of factors with anti-hemostatic, anti-inflammatory and immuno-modulatory activities. The cE5 protein was initially identified during an Anopheles gambiae salivary gland transcriptome study and later shown to share sequence similarity with anophelin, a thrombin inhibitor from the saliva of the New World mosquito Anopheles albimanus. The cE5 gene was found to encode different mRNA isoforms coexisting in several tissues of both male and female mosquitoes, a highly unusual profile for a gene potentially encoding an anti-thrombin and involved in blood feeding. Expression of the cE5 protein and assessment of its activity and inhibitory properties showed that it is a highly specific and tight-binding thrombin inhibitor, which differs from the An. albimanus orthologue for the fast-binding kinetics. Despite the widespread occurrence of cE5 transcripts in different mosquito tissues the corresponding protein was only found in female salivary glands, where it undergoes post-translational modification. Therefore, tissue-specific restriction of the An. gambiae cE5 is not achieved by transcriptional control, as common for mosquito salivary genes involved in hematophagy, but by post-trascriptional gene regulatory mechanisms. Our observations provide a paradigm of post-transcriptional regulation as key determinant of tissue specificity for a protein from an important disease vector and point out that transcriptomic data should be interpreted with caution in the absence of concomitant proteomic support.